PENGARUH SISTEM PENGENDALIAN INTERNAL DAN KOMPETENSI PERANGKAT DESA TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DESA DI KECAMATAN PADANG GELUGUR - Fatwa Ramadhan; Iskandar Sam; Misni Erwati (Jurnal Akuntansi Kompetif, 2026)
This study aims to determine the effect of the internal control system and village apparatus competency on accountability in village financial management in Padang Gelugur District. The population of this study was all villages within Padang Gelugur District, consisting of the village head, village secretary, village head (Kaur), village chief (Kasi), and village consultative body (Bamus). The sample in this study was drawn using a saturated sampling method with 52 respondents. This study used multiple linear regression analysis with the aid of SPSS version 27 for Windows. The results showed that the internal control system and village apparatus competency simultaneously influence accountability in village financial management. Partially, the internal control system influences accountability in village financial management, and village apparatus competency influences accountability in village financial management